Opposite effects of transforming growth factor alpha and epidermal growth factor on mouse placental lactogen I secretion. - Yamaguchi, M (1995)
This study was undertaken to determine whether transforming growth factor alpha (TGF-alpha) regulates the production of mouse placental lactogen I (mPL-I) and mPL-II in a manner that is similar to that of epidermal growth factor (EGF), which was previously shown to stimulate mPL-I secretion and inhibit mPL-II secretion. In contrast to the activity of EGF, human (h) and rat (r) TGF-alpha (each at 100 ng/ml) inhibited secretion of mPL-I by placental cells isolated from mice on day 7 of pregnancy. Maximum inhibition of mPL-I secretion occurred on the third day of a 5-day culture period and ranged between 37% and 56% in multiple trials. Incubation of cells with hTGF-alpha and EGF was not followed by a change in the mPL-I concentration of the medium, suggesting the peptides antagonized each other's effects. hTGF-alpha and rTGF-alpha inhibited secretion of mPL-II; maximum inhibition ranged between 62% and 84% in multiple trials. The lowest concentrations of hTGF-alpha that affected mPL-I and mPL-II secretion were 10 ng/ml and 1 ng/ml, respectively. EGF and hTGF-alpha bound to the same receptors on placental cells, as assessed by cross-linking, and both peptides stimulated receptor phosphorylation, as assessed by Western blot analysis. There are three types of mPL-containing cells in placental cultures: cells that contain only mPL-I, cells that contain only mPL-II, and cells that contain both mPLs. The percentage of each type of mPL-containing cell in the culture was determined by immunostaining. hTGF-alpha affected the differentiation of the subpopulations of PL-containing cells in a manner that differed from that of EGF. The data suggest that TGF-alpha and EGF do not regulate the production of mPL-I and mPL-II in a similar manner.